FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI DAERAH ISTIMEWA YOGYAKARTA (DIY) TAHUN 1985-2011 - Norman Luther Aruan; D Sriyono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
This study aims to identify and analyze the efect of economic growth, real minimum wages, infation and the economic crisis in Indonesia in 1998 on the unemployment rate in the Special Region of Yogyakarta (DIY) in the 1985-2011 period. The data used are secondary data obtained from the Central Bureau of Statistics published in the various editions. Te analytical tool used to answer the problem formulation is the regression analysis using partial adjustment models (PAM). The analysis and hypothesis testing show that the economic growth, infation rate and the period of economic crisis in Indonesia in 1998 have a signifcant efect on the unemployment rate in the province, while the real minimum wage has no efect on the unemployment rate in the province.Keywords: unemployment, economic growth, real minimum wages, infation rates, partial adjustment models (PAM).